2013
DOI: 10.1128/aac.01809-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of Novel Acetolactate Synthase Inhibitors as Antifungal Agents

Abstract: b High-throughput phenotypic screening against the yeast Saccharomyces cerevisiae revealed a series of triazolopyrimidinesulfonamide compounds with broad-spectrum antifungal activity, no significant cytotoxicity, and low protein binding. To elucidate the target of this series, we have applied a chemogenomic profiling approach using the S. cerevisiae deletion collection. All compounds of the series yielded highly similar profiles that suggested acetolactate synthase (Ilv2p, which catalyzes the first common step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 22 publications
(32 reference statements)
0
37
0
Order By: Relevance
“…cerevisiae was performed to identify novel antifungal compounds [26, 27]. The ergot-related compound NGx04 (Fig 1A) was among the validated hits scoring an IC 50 < 20 μM.…”
Section: Resultsmentioning
confidence: 99%
“…cerevisiae was performed to identify novel antifungal compounds [26, 27]. The ergot-related compound NGx04 (Fig 1A) was among the validated hits scoring an IC 50 < 20 μM.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been successfully applied to brewing yeast strains to increase stress tolerance (Blieck et al , ; James et al , ; Huuskonen et al , ; Yu et al , ; Ekberg et al , ) and alter the production of various flavour compounds (Strejc et al , ; Shen et al , ). Some success in altering diacetyl production has been achieved (Gjermansen et al , ), and the availability of a range of compounds that specifically inhibit the action of AHAS (Richie et al , ) suggests that this could be a potentially valuable approach for isolating natural variant strains with beneficial mutations in ILV2 or associated genes, particularly ILV6 .…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to our strategy of inducing mutations rather than selecting spontaneously resistant clones. Multiple mutagenesis experiments in fungi and mammalian cells have revealed that there is a bias towards chromosomal aberrations and SNPs in pleiotropic drug-resistance genes if spontaneous mutants are selected and sequenced (Nyfeler et al, 2012;Richie et al, 2013;Sadlish et al, 2013;Shimada et al, 2013). The underlying mechanism might be that amino acid mutations in the essential, primary target can often be deleterious, and these cells are rapidly outcompeted.…”
Section: Discussionmentioning
confidence: 99%